Die verhouding tussen Kolossense en Efesiërs as "n sinoptiese probleem - Wyk, Barry van (HTS teologiese studies, 2015)
The relationship between Colossians and Ephesians as a synoptic problem. Research by different scholars concluded that some letters traditionally ascribed to Paul were probably not written by him and drew a distinction between Pauline and Deutero-Pauline letters. The majority of scholars nowadays are of the opinion that the letters to the Colossians and the Ephesians are Deutero-Pauline and that Ephesians, at least, was surely not written by Paul. The results of research on the synoptic problem can be used and applied to the two letters under discussion because a comparison shows that there are striking similarities between the two. The most recent research shows that Ephesians made use of the letter to the Colossians but not without redactional changes to suit the author’s literary purpose. This method is exegetically known as redaction-criticism, linked to the social-science viewpoint that the author of the letter to the Ephesians acted as a change agent on behalf of a change agency.